Problems in using the wireless village services in Malaysia: the non-users perspectives - Sahharon, Hamizah; Bolong, Jusang; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2017)
This study aims to identify problems faced by rural community in Malaysia in using the wireless village services. The study is quantitative in nature and was conducted in four districts in Malaysia, namely Setiawan (Perak), Bahau (Negeri Sembilan), Marang (Terengganu) and Kundasang (Sabah). With a total of 300 respondents the study used a survey method to identify the problems faced by an ICT project called 1Malaysia Wireless Village. Analysis performed has confirmed on four main problems that were possibly affected the progress of rural development and digital equality towards economic development. A number of discussions have been highlighted and it is a hope that it can assist the concern parties in constructing the best ICT usage strategies particularly among the rural community.